Strategi Peningkatan Adopsi Inovasi pada Peternakan Sapi Perah Rakyat di Daerah Istimewa Yogyakarta, Jawa Tengah, dan Jawa Timur - Septi Nur Wulan Mulatmi; Budi Guntoro; Budi Prasetyo Widyobroto; Sudi Nurtini; Ambar Pertiwiningrum (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
This study was aimed to formulate strategies for increasing adoption innovation in the smallholder dairy farms. The study was conducted in May to July 2015. The research was conducted using survey method. The selection of respondents was conducted using multi-stage sampling to 270 dairy smallholder farmers in Yogyakarta Region, Central, and East Java Provinces. The method used was descriptive qualitative by using SWOT analysis (strength, weakness, opportunity and threat). The results of the research which is to optimize resources; provide a clear and continuous information about innovation; facilitate access to information by extending the dissemination of information; provide mentoring programs, counseling, and training with a demonstration of the innovation; increase the participation of dairy farmers; strengthen institutional dairy farmers; seek a tool to support innovation together; improve the quality of extension, media, and the delivery of information; and optimize government and NGO aid.